Role of Magnetic Rsonance Imaging (MRI) in Grading Supratentorial Gliomas Comparable with Pathology - bador, foaz; esa, rna; Haydar, Nisrin (Latakia University Journal -Medical Sciences Series, 2020)
Objective: Gliomas are one of the most common brain tumors in adults with poor prognosis in most patients. Imaging plays a critical role in the diagnosis ,management and follow up of gliomas. The aim of this study was to determine sensitivity and specificity of MRI as a diagnostic tool for supratentorial gliomas in comparison with histopathological findings Methods: Our study included 39 patients with MRI supratentorial gliomas whose age between 40-75 years in one year 2018-2019 in Neurosurgery department in Tishreen University Hospital in Lattakia. Tumors were sent for histopathological typing and grading according to the WHO 2016. Results: All of supratentorial gliomas were hyperintense in T2,while (95%) of them were hypointense in T1, in FLAIR all tumors were hyperintense , heterogenous enhancement in high grade gliomas, other radiologic findings such as: necrosis, hemorrhage and edema were common in high grade gliomas. Agreement between histological findings and MRI was 72% with sensitivity 100% and specificity 95% Conclusion: MRI plays an essential clinical role in initial diagnosis and grading of supratentorial gliomas with high sensitivity and specificity comparable with histological findings. هدف الدراسة: تعد الأورام الدبقية من أورام الدماغ الأولية الأكثر شيوعاً عند البالغين و يكون الانذار سيء لدى معظم المرضى ،تلعب تقنيات التصوير الطبي بMRI دوراً هاماً في تشخيص الأفة وتوجيه الاجراءات العلاجية، وتهدف هذه الدراسة لتحديد حساسية و نوعية ال ـMRI كاختبار تشخيصي للأورام الدبقية فوق الخيمة مقارنة مع الموجودات النسيجية. طرق البحث: تم إجراء دراسة تحليلية مقطعية عرضانية لـ 39 حالة من الأورام الدبقية فوق الخيمة ممن تتراوح أعمارهم من 40-75 سنة من مراجعي قسم الجراحة العصبية في مشفى تشرين الجامعي في اللاذقية بين عامي 2018-2019، تمت دراسة التوافق بين نتائج الرنين والتشريح المرضي مع الاعتماد على تصنيف (WHO2016) لتصنيف الأورام نسيجياً. النتائج: أعطت جميع الأورام الدبقية اشارة عالية في T2، وبينما أعطى 95% منها اشارة ناقصة في T1 لوحظ في FLAIR أن جميع الأورام كانت عالية الإشارة الأورام عالية الدرجة أعطت تعزيز غير متجانس ومظاهر التصوير الأخرى بالرنين مثل النزف، النخر، الوذمة شائعة مع الدرجات العالية للورم. بلغت درجة التوافق بين نتائج التشريح المرضي والرنين 72% ووصلت حساسية التصوير بالرنين المغناطيسي 100% بدقة 95%. الاستنتاجات: يساعد الرنين في وضع تشخيص مبدئي وتحديد درجة الأورام الدبقية بحساسية ونوعية عالية مقارنة مع الدراسة النسيجية ويمكن أن يستخدم بشكل موثوق في الممارسة السريرية وفي الحالات التي يكون فيها إجراء الخزعة غير ممكن.